Síntese e otimização de compositos de ferro e bismuto para a fotodegradação de poluentes orgânicos - Costa, Kaio Reis (2025)
The increasing contamination of water bodies by detergents, with linear sodium alkylbenzene sulfonate (LAS) as the main component, constitutes a major environmental challenge. This research analyzed the synthesis and optimization of iron and bismuth oxides for application in heterogeneous photocatalysis, aiming at the degradation of the detergent, having as a parameter to determine whether the destruction of the detergent molecules occurred the decrease in their absorbance and fluorescence. The composites were synthesized via the sol-gel route using iron nitrate, bismuth nitrate and pectin present in orange peel. The synthesis variables were the calcination temperature (500; 550; 600; 700; 800 °C) and the Bi/Fe molar ratio (0; 0.25; 0.5; 0.75; 1.0; 1.25). X-ray diffraction revealed the formation of a multiphase system with BiFeO₃, Bi₂Fe₄O₉, α-Fe₂O₃ and γ-Fe₂O₃. Presenting up to 88% BiFeO₃ in the bismuth-rich sample and 98% α-Fe₂O₃ in the iron-rich sample. Scanning electron microscopy (SEM) demonstrated the formation of a “flower-like” morphology for samples calcined between 500 and 600 °C. The degradation efficiency via photocatalysis was quantified in a solution of 100 mg/l of liquid detergent, using LEDs from a discarded television and 15 mg of iron-bismuth composite as radiation source. Among all the samples, the one produced with 0.5 mol of iron for 1 mol of bismuth and calcined at 500°C was the one that decreased absorbance the most, by more than 40%, with a reduction of more than 10% in fluorescence